Foreign and security policy in the European Union - Eliassen, Kjell A. (Western Europe Ser., 1998)
This book provides a comprehensive overview of why European integration in foreign and security policy has proved so difficult. The obstacles to developing the common policy in this second pillar of the European Union go to the heart of debates around the sovereignty of the nation-state. A leading group of international contributors explain how these problems arise and consider the future prospects of developing a more regional-based solution. Broadly organized around the three areas of policy, actors and issues, the first section traces the reluctant growth of EU integration in foreign and se.